Cholera due to exposure in Europe associated with consumption of holy water from Ethiopia, January to February 2025 - Hilary Kirkbride (Eurosurveillance)
In February 2025, public health agencies in Germany and the United Kingdom (UK) reported four cases of domestically acquired cholera caused by consumption of holy water imported from Ethiopia, and a further three cases in travellers to Ethiopia. Multidrug-resistant Vibrio cholerae O1, linked to recent outbreaks in Eastern and Middle Africa, was detected in clinical specimens and the holy water. In cholera-endemic regions, visitors should drink potable water and should not bring bottled water back from their travels.